2009
DOI: 10.1002/jcb.22007
|View full text |Cite
|
Sign up to set email alerts
|

Low magnitude and high frequency mechanical loading prevents decreased bone formation responses of 2T3 preosteoblasts

Abstract: Bone loss due to osteoporosis or disuse such as in paraplegia or microgravity is a significant health problem. As a treatment for osteoporosis, brief exposure of intact animals or humans to low magnitude and high frequency (LMHF) mechanical loading has been shown to normalize and prevent bone loss. However, the underlying molecular changes and the target cells by which LMHF mechanical loading alleviate bone loss are not known. Here, we hypothesized that direct application of LMHF mechanical loading to osteobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 40 publications
(69 reference statements)
0
48
0
Order By: Relevance
“…Recently, the RPM is used as a simulator for microgravity in various studies investigating responses in animal cells (for example Grimm et al 2002;Uva et al 2002;Infanger et al 2006;Pardo et al 2005;Patel et al 2009;Meloni et al 2006). However, the mode of operation of the RPM that was used in these studies varies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the RPM is used as a simulator for microgravity in various studies investigating responses in animal cells (for example Grimm et al 2002;Uva et al 2002;Infanger et al 2006;Pardo et al 2005;Patel et al 2009;Meloni et al 2006). However, the mode of operation of the RPM that was used in these studies varies.…”
Section: Discussionmentioning
confidence: 99%
“…They again found that ALP, Runx2, PthR1 were down-regulated in simulated microgravity. They also found that low magnitude and high frequency (LMHF) mechanical loading (0.1 ~ 0.4 g at 30 Hz for 10 ~ 60 min/day) prevented a decrease in ALP, Runx2, PthR1, but static conditions had no effect (Patel et al, 2009). …”
Section: Microarray Analysis Of Microgravity Exposed Bone Cellsmentioning
confidence: 96%
“…This may suggest that ERK1/2 is an essential pathway in the mechanotransduction process. We therefore hypothesized that ERK1/2 activation may also play an essential role in LMHF vibration mediated-BMSC osteodifferentiation.Here, it is relevant to note that the in vitro data presented in two studies by Lau et al (2010) and Patel et al (2009) to provide an explanation for the anabolic and anti-resorptive role of LMHF vibration observed in vivo, are obtained from bone cells in two dimensional (2D) cultures. However, investigating the role of LMHF vibration on osteogenic cells in 3D cultures might mimic in vivo conditions.…”
mentioning
confidence: 99%
“…Interestingly, microvibration can enhance the peak levels of these genes and intensify the pattern occurred in osteogenic differentiation. The observation could thus prove that microvibration is benefi cial for osteogenesis.3D culture has been demonstrated to promote cell osteogenic differentiation and mineralisation (Kinoshita et al, 1999;Rattner et al, 2000). To test the advantage of 3D culture on osteogenic differentiation in response to LMHF vibration, ALP activity was measured on day 14.…”
mentioning
confidence: 99%